Assessing the Impact of Green Accounting, Environmental Performance, and Asset Turnover on Profitability: A Study of Indonesian Food and Beverage Firms - Mella Sri Kencanawati; Syntha Noviyana; Yudi Andrean Syaputra (DPPM Universitas Pelita Bangsa, 2025)
Profitability is represents success, shows effectiveness in optimal use of resources, and is seen in the company's profit and economic growth. In addition, the company also has an obligation to pay attention to the environment due to the activities carried out by the company. The purpose of this study is to analyze the effect of the application of green accounting, environmental performance, total asset turnover partially and simultaneously on profitability in manufacturing companies in the food and beverage industry sub-sector for the period 2018-2023. In this study, the type of data used is quantitative data, and the data source used is secondary data in the form of company financial reports. The sample in this study is a food and beverage company, with sampling using method purposive sampling, so that produce 9 the company that used as a research sample. The analysis technique used in this study is multiple linear regression analysis. Results study in a way Partial show that green accounting And performance environment does not affect profitability, while total asset turnover affects profitability. In simultaneous testing, the results of the study showed that green accounting , environmental performance, and total asset turnover simultaneously affect profitability. This study contributes to the literature by confirming the importance of operational efficiency, as reflected in total asset turnover, as a key driver of profitability in environmentally engaged manufacturing firms, while also emphasizing the limited standalone impact of green accounting and environmental performance without operational alignment.